Reflections of Nature-Oriented Outdoor Sports Activities on Coronavirus-19 Phobia During the Pandemic Process - Sandıkçı, Muhammed Bahadır; Önen, Cihan (Progress in Nutrition, 2021)
Study Objectives: This study was carried out to evaluate the impact of participation in nature-oriented outdoor sports activities on Coronavirus-19 phobia during the pandemic process. Methods: The population of the cross-sectional study consists of 289 people who were engaged in nature-oriented outdoor sports activities in the Tunceli region between 28.06.2021 and 20.07.2021. Results: COVID-19 phobia was statistically higher in women, people under 35, singles, those with high school or lower education, and those who do not have children. Although many nature sports activities reduce the phobia of COVID-19, there was especially a statistically significant decrease in COVID-19 phobia among those who engage in rock climbing. Besides, those who practiced outdoor sports with fear of death and quarantine had a statistically higher COVID-19 phobia score. There was a weakly significant negative relationship between the years of experience, the number of types of outdoor sports activities that the individuals engage in, and the COVID-19 phobia score. As the years of experience in these activities and their types increased, the COVID-19 phobia decreased, albeit weakly. Conclusion: Performing nature-oriented outdoor sports activities from different fields can be beneficial, even partially, in reducing the phobia caused by COVID-19. In pandemics, such as COVID-19, which have a wide range of negative effects on society, individuals can be directed to nature sports against COVID-19 phobia.